The effects of identical nim gene-insertion sequence combinations on the expression of the nim genes and metronidazole resistance in Bacteroides fragilis strains - Alshateri Bakhtiyar (ANAEROBE, 2023)
In this study we examined whether the same nim gene-insertion sequence (IS) element combinations give rise to the same expression levels as they harbor shared IS element-borne promoters. From our quantitative analysis, we found that the expressions of the nimB and nimE genes with their cognate IS elements were similar, but the metronidazole resistance of these strains were more diverse.